Ethics of managers in Slovenian public administration - Nedelko, Zlatko (Faculty of Economics, Split, 2017)
The main purpose of this paper is to examine how managers´ personal values and managers´ attitudes towards the natural and social environment are shaping the ethics of those same managers in public administration. The findings are based on a sample of 212 managers from Slovenian public administration. Personal values were measured using the Schwartz value survey, while attitudes toward natural and social environment were measured with a validated questionnaire. Results show that managers´ self-enhancing values are positively related to their attitudes toward both natural and social environment and their ethics. Managers´ self-transcendence values were found to be negatively associated with their attitudes toward the social environment and their ethics. Managers´ attitudes toward natural and social environment are both positively related with the managers´ ethics. The mediation effect of the attitudes towards the social environment on the relationships between managers´ personal values and their ethics is positive and significant. The main cognition is that managers´ attitudes towards the social environment are a significantly stronger predictor of managers´ ethics than are managers´ personal values. Temeljni cilj ovog rada je utvrditi kako osobne vrijednosti menadžera u javnoj administraciji i njihovi stavovi prema prirodnom i društvenom okruženju djeluju na stvaranje njihove etike. Rezultati su dobiveni na temelju uzorka od 212 menadžera u slovenskoj javnoj administraciji. Osobne su vrijednosti mjerene uz pomoć Schwartzovog anketnog upitnika o vrijednostima, a stavovi prema prirodnom i društvenom okruženju pomoću drugog, prethodno validiranog upitnika. Rezultati pokazuju da su vrijednosti, usmjerene na povećanje vlastitog dobra/interesa, pozitivno povezane sa stavovima o prirodnom i društvenom okruženju te s etikom. Stavovi o društvenom okruženju i etici su, pak, negativno povezani s vrijednostima, usmjerenim na povećanje dobra/interesa drugih. Sami su stavovi o prirodnom i društvenom okruženju pozitivno povezani s menadžerskom etikom, a medijacijski efekt stavova o društvenom okruženju na odnos između osobnih vrijednosti i menadžerske etike je pozitivan i signifikantan. Stoga se zaključuje da su menadžerski stavovi o društvenom okruženju signifikantno značajniji prediktor menadžerske etike od osobnih vrijednosti menadžera.